2016
DOI: 10.1155/2016/4868305
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Colour Information for Computer-Aided Diagnosis of Melanoma from Dermoscopy Images: A Retrospective Survey and Critical Analysis

Abstract: Cutaneous melanoma is the most life-threatening form of skin cancer. Although advanced melanoma is often considered as incurable, if detected and excised early, the prognosis is promising. Today, clinicians use computer vision in an increasing number of applications to aid early detection of melanoma through dermatological image analysis (dermoscopy images, in particular). Colour assessment is essential for the clinical diagnosis of skin cancers. Due to this diagnostic importance, many studies have either focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 124 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…To detect melanoma at an early stage, the most subtle colour shades (especially brown) and structures need to be identified by dermoscopy, often only in a small part of the lesion [58][59][60]. Colour assessment is essential for the clinical diagnosis of skin cancers [6,[25][26][27][28][29]. Therefore, dermatologists need a dermoscopy device able to provide an image with authentic colours and sharply defined tiny structures in the lesion, as well as an image that offers the same good quality throughout the whole dermoscopic field, including at magnification [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…To detect melanoma at an early stage, the most subtle colour shades (especially brown) and structures need to be identified by dermoscopy, often only in a small part of the lesion [58][59][60]. Colour assessment is essential for the clinical diagnosis of skin cancers [6,[25][26][27][28][29]. Therefore, dermatologists need a dermoscopy device able to provide an image with authentic colours and sharply defined tiny structures in the lesion, as well as an image that offers the same good quality throughout the whole dermoscopic field, including at magnification [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Additional aspects that pose a challenge are the different colour calibrations of the cameras and different light sources, as illustrated in Fig 3 . Colour is one of the main clinical features for melanoma detection [ 5 ], and computer systems normally have one or more colour features [ 23 ]. There have been attempts at automatic colour calibration based on image content [ 24 ], but the impact on classification is not fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Different image resolutions, magnifications and distances to the skin result in the true size of the lesion differing from image to image, though this can be solved easily by providing information regarding pixels per mm. Additional aspects that pose a challenge are the different colour calibrations of the cameras and different light sources, as illustrated in Fig 3 . Colour is one of the main clinical features for melanoma detection [5], and computer systems normally have one or more colour features [23]. There have been attempts at automatic colour calibration based on image content [24], but the impact on classification is not fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a computer aided diagnostic (CAD) system is more objective. By utilizing handcrafted features, traditional CAD systems for skin disease classification can achieve excellent performance in certain skin disease diagnosis tasks [11,12,13]. However, these systems usually focus on limited types of skin diseases, such as melanoma and BCC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning methods have become popular in feature learning and achieved excellent performances in various tasks, including image classification [19,20], segmentation [21,22], object detection [23,24] and localization [25,26]. A variety of researches [9,23,12,27,25] showed that the deep learning methods were able to surpass humans in many computer vision tasks. One thing behind the success of deep learning is its ability to learn semantic features automatically from large-scale datasets.…”
Section: Introductionmentioning
confidence: 99%